Reflection of the Concept of Spivak’s Subaltern in The Nine Parts of Desire by Heather Raffo and Mastaneh, the History of the Forgotten by Naghmeh Samini - Tuba Mozafari nezhad; Esmaeil Najar (زن در فرهنگ و هنر)
This investigation applies Spivak's "Subaltern Theory" to undertake a comparative examination of Mastaneh, the History of the Forgotten and Nine Parts of Desire. Spivak maintains that comparative studies in world literature are currently predominantly conducted in accordance with the logic of globalization during the capitalist era. She is of the opinion that the field of literature is currently only used as a means to ensure the survival of Western powers. When they wish to investigate other cultures, they refer to them as "Third World" and regard them as an undeveloped "other." These criticisms are exacerbated when the Western world interacts with subordinate subjects, particularly the female gender. Due to the fact that they only provide an appearance of the situation of women in relation to their objectives. For the sake of its own objectives, it only presents a semblance of subalterns, particularly those of the female gender, and achieves an idealistic and essentialist policy. However, the subaltern subject is aware that a gender that is both expanding and developing is the most advantageous scenario for her when she speaks and behaves as a woman. It is regrettable that the subjugated and marginalized individuals should disclose another history of the oppressed, which has been neglected, in the shadow of this game. Through an examination of a selection of Spivak's theoretical works, including "Can the Subaltern Speak?"(1985), Death of a Discipline (2003), and "Rethinking Comparativism"(2009), this research will demonstrate that the Subaltern can articulate her pure experiences and self-expression through literature without the assistance of global powers, correction, or assistance.